2018
DOI: 10.1177/1747954118757437
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the anthropometric and performance characteristics of high-level youth female soccer players

Abstract: 38The purpose of this study was to evaluate the anthropometric and performance characteristics 39 of high level youth female soccer players by annual-age category (U10-U16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…36,37 However, the long-term relationship between enhancements in YYIR1 performance and physical maturation into adulthood has yet to be established in international female footballers. 38 Our study highlighted senior players covered greater total distance during the YYIR1 when compared to the U19 and U17 age groups (see Figure 1(a)) mirroring the findings of Ramos et al. 6 where senior players (1510 ± 320 m) also displayed superior YYIR1 scores versus U15 (710 ± 210 m), U17(720 ± 230 m) and U20 (860 ± 240 m) age categories.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…36,37 However, the long-term relationship between enhancements in YYIR1 performance and physical maturation into adulthood has yet to be established in international female footballers. 38 Our study highlighted senior players covered greater total distance during the YYIR1 when compared to the U19 and U17 age groups (see Figure 1(a)) mirroring the findings of Ramos et al. 6 where senior players (1510 ± 320 m) also displayed superior YYIR1 scores versus U15 (710 ± 210 m), U17(720 ± 230 m) and U20 (860 ± 240 m) age categories.…”
Section: Discussionsupporting
confidence: 85%
“…The long term athletic development of female international players should be a key priority for the player development pathways of national organisations. 38,39 The findings of this study provide age-appropriate data for coaches, strength and conditioning, and sports scientists working with elite female international players at multiple age groups. The capacity to evaluate the physical performance characteristics of female football players and compare them with age-appropriate data can aid player development pathways and individualise training programs.…”
Section: Practical Applicationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Within England, talented youth female soccer players between the ages of 8-16 years are recruited to attend Regional Talent Centre's (RTC's), with the purpose to develop players for the elite senior game. Cross-sectional data examining the physical qualities of elite youth female soccer players exists, demonstrating that physical qualities develop with increasing age (10,11,31). While cross-sectional data are useful for player monitoring and evaluation purposes, the nature of such one-off assessments fails to provide information around the development of physical qualities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Malina et al [ 24 ] showed that height, body mass and maturity status are determinants of sprint-running performance. Emmonds et al demonstrated that anthropometric and performance characteristics develop with increasing age in high-level youth female soccer players [ 25 ]. These differences in anthropometric parameters are attributed to increased maturity, biological, hormonal and neurological changes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%